Early Diagnosis and Intervention for Airway-Obstructing Neonatal Plexiform Neurofirbomatosis. Issue 5 (July 2020) - Day, Kristopher M.; Roward, Simin; Gillispie, Alexandra; Attra, James; Kelley, Patrick
Abstract : Background: Respiratory distress is a frequent occurrence in neonates, typically caused by a variety of pulmonary conditions. Accurate diagnosis of the cause is vital to appropriately treat neonates and prevent long-term complications. Neck masses rarely cause respiratory distress in this setting but should be considered when clinical signs indicate. Methods: The authors present the patient with a neonate born at term who developed stertor, respiratory distress requiring intubation, and repeated failure to extubate. Results: Physical examination showed right-sided lower and midface enlargement with a firm mass mostly over the parotid and right neck. Both computerized and magnetic resonance tomography demonstrated a right-sided neck mass. Surgical exploration revealed extensive tumor burden emanating from the great auricular, hypoglossal, and other nerves of the neck, including invasion of the carotid sheath encasing the artery. Excisional biopsy showed plexiform neurofibroma, and pathognomonic for neurofibromatosis type 1. The decision was made to pursue medical management, as complete excision would have resulted in increased morbidity due to the involvement of multiple cranial nerves. The patient underwent microlaryngoscopy, bronchoscopy, and tracheostomy and was started on Trametinib chemotherapy. Conclusion: Neonatal airway obstruction can rarely be caused by unanticipated mass lesion, such as plexiform neurofibroma. A high index of suspicion must be maintained for early onset mass lesions causing respiratory obstruction to inhibit early disease progression and avoid potentially fatal sequelae. Abstract : Supplemental Digital Content is available in the text